Current overweight but not history of gestational diabetes characterises lifestyle habits in a nationwide cohort of pregnant women - Muhli, Ella (My University, 2020)
The prevalence of overweight and gestational diabetes (GDM), glucose intolerance first manifesting during pregnancy, are increasing. Both are known to predispose mother and child to health complications. The aims of the study were to evaluate the impact of prior GDM and overweight/obesity on overall dietary quality and physical activity during pregnancy. We hypothesized that women with a history of GDM have a good dietary quality and higher physical activity, as they have previously received lifestyle counselling, and overweight/obese women have worse lifestyle habits than normal weight women. Pregnant women (n=1034) across Finland filled in an electronic questionnaire inquiring dietary and physical activity habits, health status and social background before 28 weeks of gestation. Under a half of the studied women had a good dietary quality and nearly a half had a light physical activity level. The Index of Diet Quality (IDQ) score or physical activity levels did not differ between the women with and without a history of GDM. The overweight/obese women presented with a lower IDQ score and lower physical activity levels than the normal weight women. The results highlight the need for new means to promote healthy lifestyle changes in pregnant women, especially in overweight and obese women and women with a history of GDM, since these groups are at risk for complications during pregnancy and beyond.
Keywords: gestational diabetes, obesity, diet, physical activity